Urban development in Freiburg, Germany – sustainable and neoliberal? - Mössner, Samuel (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
In recent years, sustainable urban development has emerged as a relevant but contested field in urban studies. A broad and diverse literature has discussed sustainable development from various perspectives. Some authors have researched urban sustainability from a technocratic perspective, looking for technical and managerial solutions. Others have shed light on the political dimension of urban sustainable development in our times of urban neoliberalization. This branch of literature focuses on the problematic relationship between market-oriented growth on the one hand and aspects of equality and justice on the other hand, which come along with the idea of sustainability. This article argues that the professionalization and new forms of urban management, as well as a shift towards urban governance and citizens’ participation have intensified consensual practices of urban regulation. Sustainable politics that have occurred in many cities around the world place emphasis on justice, tolerance and participation as the principal drivers for urban development. Empirical evidence shows, however, that these goals are subjugated to economic growth. Drawing on empirical work carried out in Freiburg, Germany – a city long hailed as a forerunner of urban sustainable development – this article promotes the opinion that the idea of ‘sustainable development’ in its current form is nothing more than an oxymoron, aimed and invented as a fuzzy concept in order to disguise the fundamentalist believe in growth that lies beyond such development.